CONUT score is associated with short-term prognosis in patients with severe acute pancreatitis: a propensity score matching cohort study - Shi, Lvyuan; Li, Ping; Wang, Lietao; Wan, Dingyuan; Wang, Daojin; Yan, Xin; He, Min; Zhang, Zhongwei (Frontiers in Nutrition, 2023)
Background: The Controlling Nutritional Status (CONUT) score was designed to assess the immune-nutritional status in patients. The aim of this study was to investigate the role of CONUT score in the short-term prognosis of severe acute pancreatitis. Methods: This is a retrospective cohort study. 488 patients with severe acute pancreatitis at the Department of Critical Care Medicine of the West China Hospital of Sichuan University (Chengdu, China) were enrolled in the study. Baseline data were collected from the West China Hospital of Sichuan University database. The primary outcome during follow-up was all-cause mortality. The secondary outcomes were 28-day mortality, renal insufficiency, LOS in ICU and LOS in the hospital. Patients were divided into two groups based on a median CONUT score of 7, and baseline differences between the two groups were eliminated by propensity matching. Univariate Cox regression analyses were performed to estimate the association between CONUT score and outcomes. The Kaplan-Meier method was used to estimate the survival rate of patients. Results: CONUT score was an independent predictor of all-cause mortality (hazard ratio [HR]:2.093;95%CI:1.342-3.263; p<0.001) and 28-day mortality (hazard ratio[HR]:1.813;95%CI: 1.135-2.896;p<0.013). CONUT score was not statistically significant in predicting the incidence of renal insufficiency. The high CONUT group had significantly higher all-cause mortality (p<0.001), and 28-day mortality (p <0.011) than the low CONUT group. Conclusion: The CONUT score is an independent predictor of short-term prognosis in patients with severe acute pancreatitis, and timely nutritional support is required to reduce mortality in patients with severe acute pancreatitis.